The conqueror's gift. Roman ethnography and the end of antiquity. - Merrington, John (Journal of Ecclesiastical History, 2026)
The article focuses on Michael Maas's book *The Conqueror’s Gift*, which examines the transformation of ethnographic thought in the Mediterranean world from the third to seventh centuries CE, emphasizing the impact of Christianity on Roman identity and perceptions of ethnicity. Maas argues that Christianization shifted the criteria for political and social belonging from Greco-Roman civic norms to orthodox Christian faith, introducing a teleological view that all nations were destined to join the Church. The book explores diverse sources, including ethnographies, legal codes, and theological texts, highlighting how Christian doctrine reshaped ideas about ethnicity, heresy, and the natural world. While the work breaks new ground in scope and nuance, it leaves some areas, such as gender, the cult of saints, and the post-Justinianic renegotiation of identities, less developed. Overall, Maas’s study contributes significantly to late antique historiography by bridging scholarly divides and offering a complex picture of identity formation during this period.